THE OPPRESSED BODY: AN ANTROPOLOGICAL BOARDING OF THE BODLY (Fiep Bulletin - online, 2014)
The human body has been treated as mere instrument in the current context in our society, where the mechanist vision prevails in detriment of the holistic vision. The capitalist system privileges the minority that generally withholds the power in detriment of the great majority that finds oppressed, composed for the poor people, the blacks, the women, the special carriers of necessities, and the homosexuals, among others that are discriminated. And to have progress, the detainers of the power in its majority do not hesitate in degrading the nature and explore "more weak", who, for having faith, wait for a reward after death and than they accommodate for thinking that nothing can be done. In view of this oppression suffered by the body, a revolution in our educational system becomes necessary, therefore it will only occur to the transcendence through the formation of critical and solidary human beings, and this will only be possible with a significant learning where the body pass to be treated in all its integrity, and the discipline physical education will have to consider the reason of any motor gesture, therefore thus through an education in which the body is only understood in its totality the release of the oppressed body will leave of being an utopia. This is the objective of this article to point the oppression that the human body comes suffering due a mechanist vision.
Keywords: Bodly; Education; Physical Education